Are Islamic Banks Really More Solvent Than Conventional Banks in a Financially Stable Period? - Haddad, Achraf; Ammari, Anis El; Bouri, Abdelfettah (Asian Journal of Empirical Research, 2019)
The knowledge value produced by this research was established in particular by the methodological challenges of the comparative study. Based on a process of bibliographic research, available conditional observation and the using of the Financial Ratio Analysis Method, the objective of this article is to solve the ambiguity of previous comparative research and innovated an equiprobable comparison between the solvencies of conventional and Islamic banks over the period (2010-2018). Our study is not only a matter of dealing generically with the financial solvency of conventional and Islamic banks but also, we analyzed the inherent implications that may alter the results of a banks’ operative evaluation. Two samples were taken from two reference populations existing in the selected countries. The choice of banks is limited to countries whose banking systems incorporate both Islamic and conventional banks. Subsequently, each list bank was reduced based on qualitative and quantitative filtering criteria. Therefore, each conventional bank has its closest Islamic equivalence. This restriction reduced the sample size to 63 banks each. The selected banks are all large and listed in different stock exchanges. In conclusion, we found that conventional banks are more solvent than Islamic banks during a financial stable period.